Cellular automata simulation of interrupted plasma aphaeresis on AIDS patients: Investigating effects of different clearance rate - Moonchai,S. (North Atlantic University Union NAUN, 2015)
The use of a combination of three or more antiretroviral drugs, called the Highly Active Antiretroviral Therapy (HAART), has been found to keep the viral load of HIV in the patient's body at a controllable level as well as improve the immune system. However, if HAART is abandoned, a rebound of plasma viral load occurs which led us to believe that the use of this treatment is associated with metabolic side effects in human, including increased risk for opportunistic infections. In order to avoid the problems with drug treatment, an alternative treatment by Aphaeresis has been suggested. In plasma aphaeresis, the virus in the large molecular components of plasma are removed from a patient after which the small molecular components of plasma and cell components of blood are returned to the patient. Several studies seem to suggest that plasma aphaeresis could be a good treatment for AIDS patients with peripheral polyneuropathy since plasma pheresis has been found to be capable of reducing a patient's plasma viral load to half of the original load. In this paper, we modify the CA rules based on the CA model of Moonchai and Lenbury [1] to investigate the action of plasma aphaeresis therapy on the CD4+ T cells and viral load in both the lymph node and blood compartments. Effects of different clearance rates of plasma aphaeresis therapy are investigated.